'Who is zooming who'? A study of young PE-students in their figurations. Issue 5 (13th June 2019) - Nielsen, Stine Frydendal; Thing, Lone Friis
ABSTRACT: The article presents an analysis of 93 essays written in an upper secondary school context. The essays were collected in relation to a larger research project, which went on for 5 years in a Danish upper secondary school (2010–2015). The material represents both genders and the students are 15–17 years old. We deploy a theoretical framework taken from Norbert Elias' notion on established-outsider relations [Elias, N., & Scotson, J. L. (1994 [1965]). The established and the outsiders . London: SAGE] as well as his use of personal pronouns [Elias, N. (1978). What is sociology? London: Hutchinson, Elias, N. (2001). The society of individuals . New York: The Continuum International Publishing Group] in illustrating how people negotiate, position and navigate within figurational contexts [Elias, N. (1994 [1939]). The civilizing proces. Oxford: Blackwell.]. We do this in an effort to interpret how young people negotiate 'we-I-relations' when it comes to their sporting identity. Elias' processual framework provides a tool for a much needed analysis of how young people continually orientate and develop their sense of selves. The web of human interdependencies and processes of change are key words when it comes to understanding the social practices and doings of the students' constructions of self-steering. What social scientists may see as laziness and drop-outs of sports [Seippel, Ø. (2016). Prek, vekker og kjedelig? Trening og mening blant ungdom: 1985–2013. In Ø. Seippel, M. K. Sisjord, & Å Strandbu (Eds.), Ungdom og Idrett . Oslo: Cappelen Damm Akademisk] can in the essays of students be analysed as a struggle for group connectedness and social inclusion in the classroom. The results of our research show that identity is a multiple concept and an ongoing process of emotional work [Elias, N. (1987). On human beings and their emotions: A process-sociological essay. Theory Culture Society, 4, 339–361], but also a power balance of playing and presenting what is imagined as the right performance as not being shamed as outcasts.